Impact of a Provider Communication Training Intervention on Adolescent Human Papillomavirus Vaccination: A Cluster Randomized, Clinical Trial. (4th October 2017) - O'Leary, Sean; Pyrzanowski, Jennifer; Lockhart, Steven; Barnard, Juliana; Campagna, Elizabeth; Garrett, Kathleen; Fisher, Alison; Dickinson, Miriam; Dempsey, Amanda
Abstract: Background: Effective human papillomavirus (HPV) vaccines have been available in the US for several years but are underutilized. Provider communication about the vaccine is a key factor influencing uptake, yet effective communication tools are lacking or untested. Our objective was to evaluate the impact of a Motivational Interviewing-based 5-component provider HPV vaccine communication intervention on adolescent HPV vaccine uptake. Methods: This was a cluster randomized controlled trial of 16 primary care practices in the Denver area that included 188 medical providers and 43, 132 adolescent (11–17 years old) patients. The 5-components of the intervention included an HPV fact library to create practice-specific HPV fact sheets, a tailored parent education website, HPV-related disease images, an HPV vaccine decision aid, and 2 hours of in-person communication training on using a presumptive vaccine recommendation followed by Motivational Interviewing (MI) if parents were vaccine hesitant. Each practice participated in a series of 4 intervention development meetings over a 6 month period (8/2014 – 1/2015) before launching the intervention. Primary outcomes were differences between control and intervention practices over time (i.e., "difference in difference" (DID)) in HPV series initiation (≥1 dose), and completion (≥3 doses) among 11–17 year old patients seen between 09/01/2013-08/31/2014 and 2/1/2015-1/31/2016. Vaccination data were obtained from clinics' records and augmented with a state immunization registry. Results: Adolescents in the intervention practices had a significantly higher odds of HPV series initiation over time than those in control practices (DID Adjusted Odds Ratio (AOR) 1.46, 95% Confidence Interval (CI) 1.31–1.62) and completion (AOR 1.56, 95% CI 1.27–1.92). This translated into a 9.5 absolute percentage point (PP) increase in HPV series initiation, and a 4.4 PP increase in HPV series completion in intervention practices over control practices. The intervention had a greater impact in pediatric compared with family medicine practices, and in private practices compared with public. Conclusion: Implementation of a 5-component HPV vaccine provider communication intervention significantly improved HPV vaccine series initiation and completion among adolescent patients. Disclosures: A. Dempsey, Merck, Pfizer, Sanofi pasteur: Consultant, no research funding